SOCIOLINGUISTIC ASPECT OF ECONOMIC TERMS IN UZBEK AND ENGLISH PRINT JOURNALISM - Rakhmatov Islombek Kuldosh oʻgʻli (Bright Mind Publishing, 2025)
A reader opens a business page and immediately meets a dense cluster of terms – IPO, stakeholder, start-up, marketing, alongside Uzbekized forms such as marketing, brend, or hybrid spellings shaped by Latin–Cyrillic competition. This article examines how business terminology functions as social meaning in print journalism, comparing English-language business press conventions with Uzbek print-media practices. The central claim is that business terms in newspapers do more than “name” economic realities: they also index authority, modernity, expertise, institutional alignment, and audience boundaries. The study draws on open-access normative and scholarly sources and applies a qualitative, non-corpus methodology based on close reading, contextual interpretation, and pragmatic-sociolinguistic coding. The results describe five recurring sociolinguistic functions of business terms in print news: (1) prestige and global alignment, (2) expertise signaling and gatekeeping, (3) institutional accountability and evidential positioning, (4) standardization pressure versus market-driven variation, and (5) audience design through simplification, paraphrase, and translation choices. The discussion links these patterns to language policy and orthographic regulation in Uzbekistan, and to sociolinguistic theories of symbolic power, indexicality, and mediatized change.
Keywords: Business terminology, Uzbek print media, English business press, loanwords, language policy, audience design, indexicality.